Growth Performance of Rice Under Different Water and Nitrogen Management - Othman, Sariam (2004)
The present global water crisis threatens the sustainability of irrigated rice production as the demand for available water from urban and industrial sectors is likely to receive priority over irrigation for agriculture. It may necessitate the adoption of rice production practice that reduces water input without impairing yield. Besides water, nitrogen (N) is also an important factor, which often interacts with water and influence rice growth. The study was undertaken in a series of five greenhouse experiments, to determine the effects of water management on rice growth and N uptake efficiency and to evaluate N fertilizer management on growth, yield and N use efficiency of rice grown under different water management. The three water management treatments studied were flooded, non flooded (NF)-saturated and NF-field capacity, whereas the N management practices evaluated were N rate, source, split and placement. iii Experimental results showed that rice growth , grain yield, dry root biomass, total root length, root length density, plant N uptake and N fertilizer recovery were not significantly different between flooded and NF-saturated conditions, but were significantly lower under NF-field capacity condition. Grain yield was 57.6 and 54.4% lower under NF-field capacity than flooded and NF-saturated conditions, respectively. A higher grain yield and plant N uptake response to N application rate was observed under flooded and NF-saturated than NF-field capacity condition. The estimated N rate for maximum grain yield was 99, 105 and 126 kg ha-1 for flooded, NF-saturated and NF-field capacity conditions, respectively. Nitrogen use efficiency decreased with the increasing N rate, and was significantly lower under NF-field capacity.